Stability of new varieties for yield components in rabi sorghum (Sorghum bicolor) - PRABHAKAR, PRABHAKAR; ELANGOVAN, M; RAUT, M S (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2004–07 to evaluate promising rabi (winter) sorghum (Sorghum bicolor (L.) Moench) to identify suitable genotypes for earliness, high grain and fodder yields. Genotype × environment interactions in 22 rabi (winter season) sorghum varieties were studied over 3 environments for flowering, maturity, grain and fodder yields. Significant differences were observed among environments and varieties for the characters. The G × E interactions for the characters was significant and the significant mean squares due to environment (linear) indicated the existence of real varietal differences in characters for regression over the environmental mean. The varieties, namely ‘SLV 15’, ‘SLV 29’, ‘SLV 45’ and ‘CRS 1’ were found stable for earliness and they can be directly used for breeding earliness. For improvement of grain yield, the varieties ‘SLV 40’, ‘SLV 43’, ‘SLV 44’, ‘SLV 50’ and ‘SLV 51’ were the most stable under rainfed situation. For both grain and fodder yields, the stable varieties were ‘SLV 40’, ‘SLV 43’, ‘SLV 44’ and ‘SLV 51’.